The Shared User File of the University Libraries in German Speaking Switzerland as a Tool for Cooperation - Ulrich Niederer (Liber Quarterly: The Journal of European Research Libraries, 2006)
The seven universities in the German speaking part of Switzerland started to evaluate jointly a new library management system in 1996. During that evaluation they also decided to form the IDS, the Informationsverbund Deutschschweiz (Information Network of German speaking Switzerland) in order to facilitate cooperation in 1996. It was decided to acquire Aleph 500 from Ex Libris, and projects of cooperation concentrated on two areas: catalogue (including searching the catalogues) and user services. The ‘Shared’ or ‘Single User File’ (SUF) is at the centre of the latter.